PELAKSANAAN NILAI KARAKTER RELIGIUS PADA ANAK USIA 4-6 TAHUN DI TAMAN KANAK-KANAK PLUS MARHAMAH PARUPUK TABING PADANG - Rahmadani, Melia; Mahyuddin, Nenny (IAIIG Cilacap, 2019)
This study aims to look at the description of the implementation of religious character values in children aged 4-6 years at TK Plus Marhamah Parupuk Tabing Padang. Researchers look at the implementation of religious character values from several aspects that exist (beliefs, worship, appreciation, and knowledge). Descriptive research, with a qualitative approach. To find out what the description of the implementation of religious character values in children aged 4-6 years in Kindergarten Plus Marhamah Parupuk Tabing Padang. Subjects in the study were children aged 4-6 years who were in class B1 TK Plus Marhamah Parupuk Tabing Padang. Informants from the study are Kindergarten Plus Marhamah Parupuk Tabing Padang teacher. The results showed that the implementation of religious character values in children aged 4-6 years developed well. Where the child is able to believe in the existence of God through His creation, the child can carry out daily worship, the child can fervently pray before learning, the child is able to know the way and order of worship.